Etika profetik dalam cerita rakyat Kabupaten Berau “Si Kannik Barrau Sanipa” - Satryo Kusuma Wibowo; Muhammad Abdullah (Universitas Mulawarman, 2023)
This research focuses on analyzing the form of prophetic ethics in the folktale “Si Kannik Barrau Sanipa.” This research aims to describe the form of prophetic ethics in the folktale. The forms of prophetic ethics include humanism, liberation, and transcendence. The folktale “Si Kannik Barrau Sanipa” studied is a story transcribed into a book entitled “Cerita Rakyat Paser dan Berau.” The folktale “Si Kannik Barrau Sanipa” is one of the folktales originating from Berau Regency, East Kalimantan. The method used in this research is descriptive qualitative. Data were obtained using reading and note-taking techniques. The theory used in the research is the prophetic literature study initiated by Kuntowijoyo. The research results found three forms of prophetic ethics: humanism, liberation, and transcendence, in the folklore “Si Kannik Barrau Sanipa.” The discovery of the form of prophetic ethics in folklore originating from Berau Regency, namely “Si Kannik Barrau Sanipa,” is one indicator to show that folklore is feasible or can be used as an educational medium to instill character in the younger generation, especially Islamic values based on prophetic ethics.